Pengelolaan Endowment Fund di Perguruan Tinggi Malaysia: Studi Kasus di Universitas Teknologi Malaysia - Muhammad Munadi (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2017)
This article aims to determine the historical development, management, the mechanism of collection, and distribution of endowment funds in UTM of Malaysia. The results show that the UTM endowment fund has been initiated through the RM 1 movement per student as well as expanded for lecturers and staff and fundraising from the company. Endowments fund has a fundraising program through every student to contribute RM 1.00, sponsored book by UTM publisher, Eternal Endowment Tower, golf tournament, recruitment alms during Ramadan and Idul Fitri and investment in finance and trust fund units. The income generation mechanism from donations are dominant than sources from projects and investment returns. Income derived from the project is greater than the income originating from the investment. The endowment fund distributors are identical to the distribution of scholarships.